The experiences of consumers, clinicians and support persons involved in the safety planning intervention for suicide prevention: a qualitative systematic review and meta-synthesis - Edward O’Connor; Edward O’Connor; Kate Rhodes; Nicholas Procter; Mark Loughhead; Alexandra Procter; Julie-Anne Reilly; Sophie Pettit; Monika Ferguson (Frontiers in Psychiatry)
BackgroundThe Safety Planning Intervention (SPI) is an efficacious brief intervention for supporting people experiencing suicidal ideation and behavior. However, the subjective experiences of those who have used the SPI have not been systematically evaluated. This systematic review synthesized qualitative evidence regarding the experiences of people involved in the SPI.MethodSystematic searches of international, peer-reviewed, English language literature were conducted in seven databases (CINAHL, Embase, Emcare, MEDLINE, PsycInfo, Scopus and Web of Science).ResultsA total of 588 articles were screened for eligibility, with screening, data extraction, and critical appraisal conducted in duplicate. Qualitative data were extracted from 10 included studies and synthesized via meta-aggregation. Ninety individual findings were aggregated into 14 unique categories, with categories subsequently combined to produce four synthesized findings: acceptability and positive outcomes associated with the SPI; maximizing the effectiveness of the SPI; navigating the involvement of support persons in the SPI process; barriers and limitations associated with the SPI.DiscussionCollectively, findings indicate that the SPI is viewed as beneficial by users and can be enhanced through clinicians’ use of a person-centered, collaborative approach, as well as through the inclusion of support persons. Future research should seek lived experience understandings from more diverse stakeholders, particularly regarding consumers’ experiences of using the SPI during acute distress. Further research is required to investigate causal pathways between SPI engagement and improved outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022312425, identifier CRD42022312425.